2016
DOI: 10.1039/c5dt05067g
|View full text |Cite
|
Sign up to set email alerts
|

Novel aluminum–BODIPY dyads: intriguing dual-emission via photoinduced energy transfer

Abstract: Three novel BODIPY-based heterodinuclear complexes, [salen(3,5-(t)Bu)2Al-(OC6H4-BODIPY)] (6), [salen(3,5-(t)Bu)2Al-(OC6F2H2-BODIPY)] (7), and [(mq)2Al-(OC6H4-BODIPY)] (8) (salen = N,N'-bis(salicylidene)ethylenediamine, BODIPY = 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene, and mq = methyl-8-quinolinolato) were prepared and characterized by multinuclear NMR spectroscopy. The specific structures of 6-8 were also determined by single crystal X-ray analysis. In particular, the salen-based heterodinuclear complexes 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 64 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…The use of tetradentate salen as a chelating agent to the metal center would lead to the formation of stable complexes . Our group has recently exploited a series of salen-based aluminum and indium luminophores, which are highly stable in air, and systematically tuned their optical properties. Interestingly, the novel salen–Al/carbazole dyad systems showed enhanced luminescence efficiency via intramolecular energy transfer (IET) from the carbazole moiety to the salen–Al part .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of tetradentate salen as a chelating agent to the metal center would lead to the formation of stable complexes . Our group has recently exploited a series of salen-based aluminum and indium luminophores, which are highly stable in air, and systematically tuned their optical properties. Interestingly, the novel salen–Al/carbazole dyad systems showed enhanced luminescence efficiency via intramolecular energy transfer (IET) from the carbazole moiety to the salen–Al part .…”
Section: Introductionmentioning
confidence: 99%
“…Cz1 and Cz2 showed T d5 values of 367 and 406 °C, respectively, and exhibited thermal stabilities higher than those of other salen−Al complexes with stepwise thermal degradation. 26 These features could be attributed to both the rigid tetradentate coordination of salen−In parts and the robust In-methyl bonds.…”
Section: ■ Introductionmentioning
confidence: 99%
“…42 Additionally, we have reported novel salen−Al-Received: October 23, 2018 Published: January 29, 2019 based dyad systems (II and III) that feature interesting luminescent properties via IET phenomena. 43,44 On the basis of these previous results, we have found that the proper selection of both functional groups and a practical synthetic strategy can lead to attractive optical properties in salen−Al complexes. In the continuous extension of our systematic research on IET, we have taken an interest in the fact that the TPA groups can sufficiently serve as intramolecular energy hosts in a novel class of salen−Al dyad systems based on their excellent stabilities and emission in the near-UV energy region.…”
Section: ■ Introductionmentioning
confidence: 88%
“…Among these complexes, the TPA-containing alkynylgold­(III) complexes recently reported by Yam and co-workers exhibit excellent optical properties, resulting from the intramolecular charge transfer (ICT) interactions between each ligand. , Recently, we have developed carbazole-containing salen–aluminum (Al) complexes ( I in Figure ), the quantum efficiency of which is enhanced by an intramolecular energy transfer (IET) process, not by ICT . Additionally, we have reported novel salen–Al-based dyad systems ( II and III ) that feature interesting luminescent properties via IET phenomena. , On the basis of these previous results, we have found that the proper selection of both functional groups and a practical synthetic strategy can lead to attractive optical properties in salen–Al complexes. In the continuous extension of our systematic research on IET, we have taken an interest in the fact that the TPA groups can sufficiently serve as intramolecular energy hosts in a novel class of salen–Al dyad systems based on their excellent stabilities and emission in the near-UV energy region.…”
Section: Introductionmentioning
confidence: 99%
“…Commercial reagents 2‐methylquinolin‐8‐ol (q), trimethylaluminum (2.0 M in toluene), dimesitylboron fluoride (Mes 2 BF), 1‐bromo‐4‐methoxybenzene, 2‐bromo‐6‐methoxynaphthalene, 4‐hydroxyphenylboronic acid, boron trifluoride diethyl etherate (BF 3 ·Et 2 O), boron tribromide, Pd(PPh 3 ) 4 , K 2 CO 3 , and tetrabutylammonium fluoride (TBAF), were employed without any further purification after purchasing from Sigma‐Aldrich. Reagents (4‐bromophenyl)dimesitylborane, B1 , and A1 (Scheme ) were prepared according to the reported procedures. Deuterated CDCl 3 solvent was obtained from Cambridge Isotope Laboratories (Tewksbury, MA, USA) and was used after drying over activated molecular sieves (5 Å).…”
Section: Methodsmentioning
confidence: 99%